UPAYA INDONESIA DALAM MENJAGA KESELAMATAN BERNAVIGASI DAN PERLINDUNGAN LINGKUNGAN MARITIM TAHUN 2014-2018 STUDI KASUS : PERAIRAN SELAT MALAKA - Sintia, Monica; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to review Indonesia efforts to enhance safety navigation and maritime environment protection in the Strait of Malacca. The strait of Malacca has geographical conditions are narrow, shallow and also considered as one of the strategic strait in the world. The high traffic and difficult geographical condition of the use by ships very vulnerable to the marine casualties. The Straits also has a risk on the marine environmentaldisaster, since the high number of ships which passthrough the Straits could result in pollution of the waters in the Straits. Indonesia as a littoral state in Malacca Strait collaborates with several countries such as Malaysia, Singapore and then make a forum to (membahas upaya) enhance safety navigation and prevent the disruption of Malacca Strait waters by oil spills from ships. The forum (dinamakan TTEG). From this forum collaboration (TTEG) several programs and project were produced like Marine Electronic Highway (MEH), Vessl Traffic System (VTS), Joint Hydrographic Survey, Voluntary Pilotage Service (VPS), and Maintenance of Shipping Navigation Assistance (SBNP).Keywords: Efforts, Littoral State, Enhance Safety Navigation, Maritime Environmental Protection, Malacca Straits